Evaluation effects toxics of cyanide, protectión of tyosulffate of sodium on tilapia (Oreochromis sp.) (Orinoquia, 2016)
In Colombia, the mining is designed as an area of development for the country with the indiscriminate use of polluting chemicals such as cyanide, but environmental risks and public health related to this activity are high with control limitations in the analysis and monitoring exercise environmental authorities on these compounds that are considered polluting effluents and toxic for native and exotic fish. Objective. Determine the effects generals toxics of cyanide, the protect effect of thiosulfate of sodium and the variations in biochemical parameters blood in Oreochromis sp, exposed to acute concentrations of cyanide of sodium. Methods. Worked with (36) tilapia red (Oreochromis sp.), exposed for 24 h to four treatments; 1: control group (free substance); 2: 1ppm of NaCN; 3: 1ppm of NaCN and 50ppm of thiosulfate of sodium. Was assessed the general toxics effects and was take samples of blood to hematocrit and biochemical parameters (plasma proteins, glucose and lactate). The fish were euthanized and necropsied to collect fragments of liver and brain to qualitatively determinate the presence of cyanide for mean of test picric acid. The analysis and interpretation of results of the qualitative variables was performed using same description and comparison between treatments, the date of variables quantitative was compared by descriptive statistics and test tukey. Within the first 15 minutes the fishes of treatments 2 and 3 showed acute signs of intoxication as respiratory distress, hyperactivity, erratic swimming, and inability to move. The hematocrit was found high in fish treatments 2 and 3 compared to treatments 1 and 4, the glucose and lactate levels in blood was found significantly higher (p< 0.05) in the specimens of treatments 2 and 3; but the plasma protein level showed no significant difference between treatments. The result of test picric acid was not conclusive in liver and brain. Conclusion. Changes in behavior are clinical manifestations of intoxication and it is clear that the NaCN in acute exposure, markedly affects the blood biochemical parameters evaluated, that would be very useful to diagnose cases of similar symptoms and suspected cianurotoxicosis, sodium thiosulfate to doses used showed no protective effect, possibly because of the high sensitivity of the species to this toxicant concentration.
Keywords: Cyanide; glucose; lactate; tilapia red; thiosulfate of sodium